Time-resolved measurements of electron density in nanosecond pulsed plasmas using microwave scattering. (30th July 2018) - Wang, Xingxing; Stockett, Paul; Jagannath, Ravichandra; Bane, Sally; Shashurin, Alexey
Abstract: In this work, microwave scattering was utilized to measure the electron number density produced in a nanosecond-long high-voltage breakdown of air between two electrodes in a pin-to-pin configuration. The approach allows tracing the absolute electron number in the plasma volume during the high-voltage pulse and the plasma decay for wide range of plasma and discharge parameters. Electron number density decayed on the timescale of about several μ s governed by plasma-chemical processes including dissociative recombination, three-body attachment and formation of cluster ions.